2021
DOI: 10.1111/aor.14154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severe mitral regurgitation on postoperative outcome after durable left‐ventricular assist device implantation

Abstract: Background: Mitral valve regurgitation (MR) is a common finding in patients with end-stage heart failure. The aim of the study was to analyze the impact of preoperative moderate-to-severe MR on postoperative outcomes and survival after durable left-ventricular assist device (LVAD) implantation. Methods:From August 2010 to May 2021, 246 patients underwent a durable LVAD implantation. We stratified the patients into two groups: Group A (n = 109) presented with MR 0-I°, and Group B presented with MR II-III° (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Whilst our recently published meta‐analysis showed that the degree of pre‐operative MR does not appear to affect mortality in patients receiving LVAD, 24 the same cannot be said for post‐operative MR with several studies linking it to worse clinical outcomes, 25,26 a conclusion which was also reached by the recently published study by Loforte and colleagues 27 . Interestingly, the study by Loforte et al 27 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Whilst our recently published meta‐analysis showed that the degree of pre‐operative MR does not appear to affect mortality in patients receiving LVAD, 24 the same cannot be said for post‐operative MR with several studies linking it to worse clinical outcomes, 25,26 a conclusion which was also reached by the recently published study by Loforte and colleagues 27 . Interestingly, the study by Loforte et al 27 .…”
Section: Discussionmentioning
confidence: 90%
“…8,[19][20][21][22] This is believed to be a result of improving the haemodynamics of the left ventricle thus lowering the left ventricular enddiastolic diameter (LVEDD) and therefore reducing the severity of MR. 23 It is most likely because of this, that we did not find increased survival in the LVAD + MVR group. Whilst our recently published meta-analysis showed that the degree of pre-operative MR does not appear to affect mortality in patients receiving LVAD, 24 the same cannot be said for post-operative MR with several studies linking it to worse clinical outcomes, 25,26 a conclusion which was also reached by the recently published study by Loforte and colleagues. 27 Interestingly, the study by Loforte et al 27 surprisingly demonstrates that LVAD implantation in patients with significant preoperative MR without concomitant mitral valve surgery leads to better survival and morbidity outcomes compared to those with mild or no MR.…”
Section: Mortality Outcomesmentioning
confidence: 90%
“…Of these, 340 relevant articles were read in full and assessed according to our inclusion and exclusion criteria. Following critical appraisal, a total of 19 studies [7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] incorporating a total of 11 873 patients were included. The studies described outcomes of patients undergoing LVAD implantation with either MR grade 0-I (8819 patients) or II-III (3096 patients).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…52 Future efforts should focus on reducing adverse outcomes in high-risk groups, 53 such as those with concomitant TR. 54 Zuberevich et al 8 suggested the potential benefits of operative TR resolution in cases where it accompanies severe levels of pre-operative MR.…”
Section: Future Directions and Current Challengesmentioning
confidence: 99%
See 1 more Smart Citation